Exploring The Loving of Christ Through the Perspective of a Disciple - Wood, Alan; Buyung, Yopie (STT Saint Paul Bandung, 2025)
This article explores the theme of Christ's love as the central message of Scripture, highlighting its embodiment from Genesis to Revelation. The purpose is to explain that Scripture is the primary source of expressing God's love for the world through Christ. Using a biblical theological approach, this article traces how God's love drives His actions and demands a response from humans. This study yielded the main response, namely that believers must love God, their neighbor, the Savior, and their enemies. Likewise, discipleship rooted in God's love will have an impact on faith growth and spiritual maturity. In conclusion, believers as disciples of Christ must reflect on God's love as the basis for transforming Christian life personally and communally.